Aplikasi Pengambilan Keputusan Kelayakan Penerima Jamkesmas di Dinas Kesehatan Kabupaten Sumba Barat Daya Menggunakan Metode Analytic Hierarchy Process - Samuel Bili Bayo; Cecilia D.P.B Gabriel; Paulus Mikku Ate (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
The purpose of this study is to create a Decision Making Application for Eligibility of Jamkesmas Recipients at the Health Office of Southwest Sumba Regency Using the AHP Method. The high poverty rate affects all sectors of life including the health sector. The health sector has many facilities that everyone can use, depending on each person's ability. These facilities can only be used if they have enough money for the necessary facilities. So that decent health for everyone is not fulfilled. The problem of poverty is the main reason someone does not get good access in the health sector, so the role of the government is needed to guarantee the population's access to humanitarian health services. From the results of the discussion above, the author wants to conclude that with the application of a decision support system using the AHP method, it can make it easier to determine the eligibility of providing JAMKESMAS services to the community in the Health Office of Southwest Sumba Regency